Simulation and Optimization of Rectangular Microstrip Patch Antenna for Mobile 5G Communications - Hamzah M. Marhoon; Noorulden Basil; Ahmed R. Ibrahim; Hussein A. Abdualnabi (Universitas Ahmad Dahlan, 2022)
Microstrip or patch antennas are becoming increasingly useful because they can be printed directly onto a circuit board. The microstrip antennas are becoming very widespread within the mobile phone market. Patch antennas are low fabrication cost, have lightweight, and are easily fabricated. The lightweight construction and the suitability for integration with microwave integrated circuits are two more of their numerous advantages. This work introduces a design of a rectangular Microstrip Patch Antenna (MPA) at a frequency of 28 GHz using the finite integration technique of the Computer Simulation Technology (CST). The simulated antenna is employed for the 5G mobile communication. The inset-fed technique has been used to feed the rectangular MPA because it is easy to fabricate and provides simplicity in modelling as well as impedance matching. In order, to facilitate the fabrication and reach the best results, an attempt has been made to improve parameters through optimized patch dimensions by trial and error.Â A reasonable gain, bandwidth, radiation pattern, and return loss have been obtained after the antenna simulation process was completed.